Penggunaan Media Gawang Mini Terhadap Hasil Keterampilan Pembelajaran Sepak Bola Pada Peserta Didik SMP Negeri 1 Jatibarang - Farhan Harir Nazhif; Fahrudin Fahrudin; Tedi Purbangkara (Jurnal Ilmiah Wahana Pendidikan, 2023)
With the title "Use of Mini Goalie Media on the Results of Football Learning Skills for Students at SMP Negeri 1 Jatibarang" This study aims to determine whether there is a significant use of mini wicket media on the results of football learning skills in students SMP 1 Jatibarang. This research method uses an experiment with One Group Pretest-Posttest research design with a population of 319 students and a sample of 39 students, by measuring the minimum sample required, the researcher uses the Slovin formula with an error rate of 15%, probability sampling sampling technique, research method using research methods quantitatively, the normality test of this data uses the Kolmogorov-Smirnov test with a significant value using SPSS 25 for pretest and posttest data passing tests 0.05 greater than 0.05 and for pretest and posttest shooting test data 0.05 greater than 0.05 then the data is normally distributed. Based on the homogeneity test, it can be seen that the results of the pretest and posttest can be significantly greater than 0.05 with sig. P 1,000>0.05. Therefore, it can be concluded that the value is homogeneously distributed. Furthermore, the calculated T value obtained is -7.222 and for T table 1.68595. Because the value of T arithmetic > T table, it can be concluded that there is an effect of the practice of using the mini wicket media on the football learning skills of passing and shooting abilities in the soccer game of the students of SMP N 1 Jatibarang